Wide range continuously tunable and fast thermal switching based on compressible graphene composite foams - Tingting Du (Nature Portfolio, 2021)
Current designs of thermal switches are limited by a lack of continuous tunability, low switching ratio, low speed, and not being scalable. Here the authors report a continuously tunable, wide-range, fast, and cost effective thermal switching approach that is demonstrated using compressible graphene composite foams.